Fight the power : law and policy through hip-hop songs / edited by Gregory S. Parks, Frank Rudy Cooper. - Parks, Gregory, 1974-; Cooper, Frank Rudy (Cambridge University Press, 2022)
Taking inspiration from Public Enemy's lead vocalist Chuck D - who once declared that 'rap is the CNN of young Black America' - this volume brings together leading legal commentators to make sense of some of the most pressing law and policy issues in the context of hip-hop music and the ongoing struggle for Black equality. Contributors include MSNBC commentator Paul Butler, who grapples with race and policing through the lens of N.W.A.'s song 'Fuck tha Police', ACLU President Deborah Archer, who considers the 2014 uprisings in Ferguson, Missouri, and many other prominent scholars who speak of poverty, LGBTQ+ rights, mass incarceration, and other crucial topics of the day. Written to 'say it plain', this collection will be valuable not only to students and scholars of law, African-American studies, and hip-hop, but also to everyone who cares about creating a more just society.